2000
DOI: 10.4049/jimmunol.165.5.2432
|View full text |Cite
|
Sign up to set email alerts
|

T Cell Effector Function and Anergy Avoidance Are Quantitatively Linked to Cell Division

Abstract: We have shown previously that T cells activated by optimal TCR and CD28 ligation exhibit marked proliferative heterogeneity, and ∼40% of these activated cells fail entirely to participate in clonal expansion. To address how prior cell division influences the subsequent function of primary T cells at the single cell level, primary CD4+ T cells were subjected to polyclonal stimulation, sorted based on the number of cell divisions they had undergone, and restimulated by ligation of TCR/CD28. We find that individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
74
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(82 citation statements)
references
References 73 publications
7
74
1
Order By: Relevance
“…It becomes clear from the present study and others (16,17,42) that the properties of memory populations rest on the frequencies of responding cells. Previous studies using either LDA or MHCtetramer technology showed that immunization with pathogens leads to an increased frequency of Ag-specific cells (4 -8).…”
Section: Discussionsupporting
confidence: 67%
“…It becomes clear from the present study and others (16,17,42) that the properties of memory populations rest on the frequencies of responding cells. Previous studies using either LDA or MHCtetramer technology showed that immunization with pathogens leads to an increased frequency of Ag-specific cells (4 -8).…”
Section: Discussionsupporting
confidence: 67%
“…Interestingly, this effect was associated with maintained T cell responsiveness and reversal of T cell anergy and was not a consequence of simply increasing T cell numbers. This is consistent with the defined property of IL-7 and other common ␥-chain-binding cytokines to reverse T cell anergy in vitro (37,38). Our results suggest that lymphopeniainduced homeostatic proliferation is an effective method for preventing and reversing tumor-induced CD8 ϩ T cell anergy in vivo, representing a strategy that is attractive for clinical translation.…”
supporting
confidence: 70%
“…In naive mouse cells, Th1/Th2 cytokine expression is cell cycle-dependent, suggesting that the role of IL-2 is to drive such cells to cycle (61). By contrast, previously activated cells that have not undergone cell division can express CD25 and produce IFN-␥ upon restimulation to the same extent as cells that had divided earlier (62). We find in a bulk population of human PBMC that inhibiting IL-2R signaling blocks cytokine production prior to cell division and, at least for IFN-␥, this occurs both in presumably naive (CD45RA) and memory (CD45RO) cells.…”
Section: Discussionmentioning
confidence: 95%